The Polish demoscene – between the past and the future. Conversation with Łukasz Szałankiewicz - Pigulak, Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
In 2021, the National Institute of Cultural Heritage approved the application to include the demoscene in the UNESCO National List of Intangible Cultural Heritage. The Social Committee of the Polish Demoscene Chronicles was responsible for coordinating these activities. The organization aims to document and analyse traditions related to the domestic demoscene. The conversation between Marcin Pigulak (historian of digital games) and Łukasz Szałankiewicz (lecturer, multimedia artist and representative of the Polish Demoscene Chronicles) focuses on the history of the Polish demoscene, its specific nature compared to other digital cultures and contemporary strategies to preserve its heritage.